OPTIMIZATION OF BUFFER AND PRIORITIES FOR ENSURING SECURITY IN BLUETOOTH NETWORKS (Information systems and technologies security, 2025)
B a c k g r o u n d . The optimization of buffer zone size for information protection plays a crucial role in ensuring the security of video streaming over Bluetooth wireless networks, particularly given the increased data transmission speeds and the use of adaptive modulation with a three-tier buffer. Recent studies show that proper management of buffer size can significantly enhance the quality of video data transmission and reduce security threats. An important aspect of ensuring security in video streaming systems over wireless networks like Bluetooth is the integration of cutting-edge information protection technologies. Modern trends in cybersecurity encompass key elements such as data encryption, access control, and multi-factor user authentication. These mechanisms not only protect data from unauthorized access but also ensure its integrity and confidentiality at every stage of processing and transmission.M e t h o d s . The study employed analytical methods including modeling and simulation, statistical and comparative analysis, experimental research, and risk assessment, enabling a comprehensive understanding of data transmission quality management in Bluetooth networks under cross traffic conditions.R e s u l t s . Properly configuring the buffer zone size can significantly enhance the efficiency and reliability of protecting critical data from unauthorized access and cyberattacks. Modern approaches to buffer size optimization utilize traffic analysis and modeling methods, as well as machine learning algorithms to predict traffic volumes and characteristics. For instance, clustering algorithms can be employed to identify traffic types and characteristics, allowing for more efficient resource allocation and buffer space management. To effectively optimize the buffer zone size, it is essential to consider system performance and information security standards, including ISO/IEC 27001 and ISO/IEC 27002. ISO/IEC 27001 outlines requirements for information security management systems, emphasizing risk assessment and the implementation of security measures. ISO/IEC 27002 provides recommendations for data protection, such as the use of cryptographic methods. The buffer zone size must meet the requirements of cryptographic algorithms and ensure resilience against attacks such as DoS and buffer overflow, while also considering scalability and compliance with contemporary regulations.C o n c l u s i o n s . Optimizing the buffer zone size in the context of video data transmission over Bluetooth networks is a critical aspect that affects not only the stable operation of the system as a whole but also the effective management of traffic flows, allowing for improvements in information transmission quality and significantly reducing potential risks from external cyberattacks and internal failures that may arise due to cross traffic or other network anomalies. The application of adaptive signal modulation in close interaction with three-tier data buffering enables the system to dynamically adjust to variable communication channel parameters, such as transmission speed, noise levels, and interference. This, in turn, helps maintain a high level of video stream quality even under adverse environmental conditions and increased signal variability. The integration of three buffer levels, each performing distinct storage and preprocessing functions for incoming data, creates an additional protective barrier that significantly minimizes the negative impact of external factors on system stability, particularly by preventing possible delays, interruptions, or data loss that may arise due to changing environmental conditions or network impediments during information transmission.
Keywords: buffer optimization; video streaming; Bluetooth wireless networks; adaptive management; data transmission; signal quality; packet loss; user priority management; cross traffic; information protection